CLINICAL STUDY TO EVALUATE EFFECT OF MUSTADI KWATH IN MADHUMEHA - Geetika Arya,; Punita Pandey,; Priyaranjan Tewari, (International Journal of Ayurveda and Pharma Research, 2021)
The dissertation is entitled “Clinical study to evaluate the effect of Mustadi kwath in Madhumeha. Diabetes mellitus has become a dreadful disease in the era. It is also described in Ayurvedic text in terms of Madhumeha. Diabetes Mellitus is a group of metabolic disease in which there are high blood sugar levels over a prolonged period, this high blood sugar produces the symptoms of frequent urination, increased thirst, and increased hunger. Untreated, diabetes can cause many complications. Sedentary lifestyle, lack of exercise, improper medication and urbanization precipitates the disease. In the present study, Mustadi kwath (mentioned in Bhaisjya Ratnawali) was selected for clinical trial. The study comprises of 40 patients of Madhumeha. These patients were randomly selected on the basis of inclusion and exclusion criteria with detailed clinical history, physical examination and other desired investigation. The duration of study is of 90 days with 15 days follow up. After evaluating therapy it was observed that the ‘Mustadi kwath’ provided better relief to the patients of Madhumeha.